Fresno County Bar Association Luncheon with State Bar President Terry Anderlini - Watkins, Howard::::::::: (1988)
Fresno County Bar Association President Herbert Levy, State Bar President Terry Anderlini, La Raza Lawyers Secretary Joel Murillo, State Bar Board Public Member Glee Ewell, District 5 Governor Dennis Cornell, Randi Saul-Olsen Fresno County Young Lawyers Association Board Member, Executive Committee Member Peter Lewis, Fresno County Bar Association President-Elect G. Dana French